Efectos colaterales de los anticonceptivos utilizados en las madres del centro del Buen Vivir Daniel Álvarez - Iñaguazo Iñaguazo, Benilda Ofelia (2015)
There are a variety of safe, effective contraceptive methods that is needed is to find the most suitable for side effects, which bring with them many consequences and occurring at doses used for purposes therapeutic, prophylactic or diagnostic is not filed. A study of descriptive type with the aim of identifying side effects related to the use of contraceptives in the mothers of the center of good living Daniel Alvarez. A single survey for the collection of the information was applied to 30 mothers of the center of the good living Daniel Alvarez Burneo. Among the main results found that 27% of mothers use the injectable contraceptive method, 20% use the pill; introducing effects physios as weight increased by 30%, menstrual flow by 7% incremnto; also have psychological as the change of character effects 60% and the have biological effects and 40% 38% of surveyed mothers were headache, while 17% reported nausea or vomiting. In conclusion can be that mothers who use contraceptives, have collateral such as physical, psychological, and biological effects. KEYWORDS: Side effects, birth mothers.